Wireshark for security professionals using Wireshark and the Metasploit Framework - Bullock, Jessey; Gordon, Adam (Wiley, 2017)
Wireshark for Security Professionals covers both offensive and defensive concepts that can be applied to essentially any InfoSec role. Whether into network security, malware analysis, intrusion detection, or penetration testing, this book demonstrates Wireshark through relevant and useful examples.